PENCEGAHAN HIPERURESEMIA DAN OBESITAS MELALUI SKRINING KADAR ASAM URAT DAN STATUS GIZI PADA DEWASA USIA PRODUKTIF DI JAKARTA BARAT - Santoso, Alexander Halim; Gunawan, Shirly; Lo, Geoffrey Christian; Pramana Jaya, I Made Satya; Lumintang, Valentino Gilbert (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Hyperuricemia is a pathophysiological condition associated with chronic inflammatory diseases such as rheumatoid arthritis, diabetes, and cardiovascular and renal diseases. Hyperuricemia is related to lifestyle. Elevated serum uric acid levels can be a marker for metabolic syndrome which generally occurs in adults. So far it is not known what the prevalence of hyperuremia and obesity is among members of the Kodim XXX team and adults of productive age in West Jakarta. Promotion of healthy lifestyles and prevention of disease are fundamental principles behind public health and improving public health. Measuring uric acid levels can prevent acute attacks of gout. Anthropometry is a measurement method used to assess the size, proportions and composition of the human body. The results of anthropometric measurements can be used to assess nutritional status. The target of this activity is the XXX Kodim Team and the adult community of productive age in West Jakarta. The aim of this service is to obtain an overview of uric acid and nutritional status in the Kodim XXX team and adults of productive age so that they can prevent the occurrence of metabolic syndrome in the future.